RNA-Editing Enzyme-Recruiting Oligonucleotides and Uses Thereof (2022)
The present disclosure features useful compositions and methods to recruit RNA editing enzymes and treat disorders for which deamination of an adenosine in an mRNA produces a therapeutic result, e.g., in a subject in need thereof.